Regulation of T Helper Cell Fate by TCR Signal Strength - Bhattacharyya, Nayan D.; Feng, Carl G. (Frontiers in Immunology, 2020)
T cells are critical in orchestrating protective immune responses to cancer and an array of pathogens. The interaction between a peptide MHC (pMHC) complex on antigen presenting cells and T cell receptors (TCRs) on T cells initiates T cell activation, cell division, and clonal expansion in secondary lymphoid organs. T cells must also integrate multiple T cell-intrinsic and extrinsic signals to acquire the effector functions essential for the control of invading mirobes. In the case of T helper cell differentiation, while innate cytokines have been demonstrated to shape effector CD4+ T lymphocyte function, the contribution of TCR signalling strength to T helper cell differentiation is less understood. In this review, we summarise the signalling cascades regulated by the strength of TCR stimulation. Various mechanisms in which TCR stimulation strength controls T helper cell expansion and differentiation are also discussed.